Competition and cooperation in mutual fund families - Evans, Richard Burtis; Prado, Melissa Porras; Zambrana, Rafael (Journal of Financial Economics, 2020)
Using manager compensation disclosure and intra-family manager cooperation measures, we create indices of family-level competitive/cooperative incentives. Families that encourage cooperation among their managers are more likely to engage in coordinated behavior (e.g., cross-trading and cross-holding) and have less volatile cash flows. Families with competitive incentives generate higher performing funds, a higher fraction of “star” funds, but greater performance dispersion across funds. In examining the determinants of incentive schemes, competitive families are more likely to manage institutional money, and cooperative families are more likely to distribute through brokers, consistent with retail demand for nonperformance characteristics.